Identifikasi Keterlambatan Proses Stamping pada Perusahaan Rigid Plastic Packaging - Isaac Setiawan; I Gede Agus Widyadana; Karina Agustin (Jurnal Titra, 2018)
This research was conducted to find the root of problem by using CP8211 natural color product as research object. The problem was identified with using lean manufacturing philosophy concept. The 5 Whys Analysis technique is used to identify existing problems. An outline lateness can occur due to two things, namely problems in scheduling and problems in the stamping process itself. Scheduling problems, whether errors in the determination of dates or errors in determining the length of processing time, can occur due to inaccuracy of operator scheduling PT. X itself. Processing problems can occur because the machine's working efficiency does not match the minimum engine capacity of 80%. Inefficient (under 80%) machines can occur due to several factors. The inefficient causes of the engine are identified by using the Cause and Effect Diagram. The results of this study indicate that the factors causing lateness that occur due to scheduling errors in the process of up-down stamping and engine damage are suspected due to engine age of more than 10 years. The solution provided for the scheduling problem is the scheduling operator of PT. X must be more careful in recording data that has been scheduled in order to avoid misunderstandings. The solution for machine efficiency is PT. X can replace parts of the machine that often damage with a new or replace the old machine with a new one. The new machine still uses the same workings as the old machine, which involves human labor to operate it.